Rewizje historii i dyskursu kryminologicznego: Kuśniewicz, Terlecki, Rymkiewicz - Dorota Wojda (Przestrzenie Teorii)
The article concerns texts which problematize such figures of criminological discourse as crime, perpetrator, victim, interrogator, or the penitentiary system. The works of A. Kuśniewicz, W.L. Terlecki and J.M. Rymkiewicz perform multidimensional revisions: they question traditional thinking about historical truth and the means of reaching it; they trespass the border between literature and fiction; they resist criminological discourse. The writers discussed formulate a diagnosis in many aspects close to that of M. Foucault’s and the new victimology, proving that representations of history as well as mechanisms of social control are discourses of restrictive authority. Korupcja [Corruption], Odpocznij po biegu [Rest after The Race], and Wielki książę [The Grand Duke] respond to such violence with revisions of history as well as the present, thanks to which literature becomes a form of radical hermeneuti